Bioaccessibility and Intestinal Transport of Deltamethrin in Pacific Oyster (Magallana Gigas) Using Simulated Digestion/NCM460 Cell Models - Jiao, Yadan; Liu, Chune; Feng, Chunsong; Regenstein, Joe M.; Luo, Yongkang; Tan, Yuqing; Hong, Hui (Frontiers in Nutrition, 2021)
Deltamethrin (DEL) can be introduced into the food chain through bioaccumulation in Pacific oysters, and then potentially threaten human health. The objective of this study was to investigate the bioaccessibility of DEL in oysters with different cooking methods after simulated digestion. DEL content in different tissues of oysters going from high to low were gills, mantle, viscera, and adductor muscle. Bioaccessibility of DEL in oysters decreased after steaming (65%) or roasting (51%) treatments compared with raw oysters (82%), which indicated that roasting can be used as a recommended cooking method for oysters. In the simulated digestion process, the concentration of DEL in the digestive juice and the bioaccessibility of DEL were affected by the pH in the gastric phase. And the transport efficiency of DEL through the monolayer molecular membrane of NCM460 cells ranged from 35 to 45%. These results can help assess the potential harm to consumers of DEL in shellfish. Furthermore, it provides a reference for the impact of lipophilic toxins in seafood.